Dayak Tribe Talawang Motif as a Variety of Bridal Fashion Decoration with Laser Cutting Technique - Indarti Indarti; Asri Setyo Harini (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2023)
Talawang is a traditional shield belonging to the Dayak tribe. This research aimed to describe the results of the finished Talawang motif as a wedding dress decoration. The method used a double diamond consisting of 4 stages: discover, define, develop, and deliver. The results of applying the Talawang motif on bridal clothing were analyzed descriptively using the FEA (function, aesthetic, expressive) model. The laser cutting technology could detail the Talawang motif as a modern wedding dress decoration. Making the Talawang motif of the Dayak tribe uses a particular machine for laser cutting using synthetic leather. The bride's clothing follows the design concept using a mermaid silhouette, applying the Talawang motif on the dress and part of the sleeves. The finished men's clothing is under the design concept using a classic formal dress silhouette in a suit consisting of a shirt, vest, trousers, and coat, applying the Talawang motif on the right side of the suit's body. Based on the analysis of the function of the clothing created is a wedding dress, while in terms of aesthetics by applying decorations in the form of stylized Talawang motif with laser cutting techniques. This wedding dress expresses the uniqueness and beauty of the Talawang motif, expressing a modern wedding dress with a touch of local cultural values.